FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN PRODUK GREEN WORLD GLOBAL DI BANDA ACEH - Amri, Saiful (Fakultas Ekonomi dan Bisnis Islam, 2018)
This study aims to determine whether cultural factors, social, personal and psychological factors have a simultaneous and significant effect on the purchasing decisions of Green World Global products in Banda Aceh. The sample in this study amounted to 60 respondents. The sampling technique in this study is the accidental sampling technique. Research this done during one month. Analysis of the data used in this study by using validity test, reliability test, coefficient of determination analysis, simultaneous test, formal test, from the results of test conducted found that all cultural, social, personal and psychological factors have no significants effect on product purchase decision making Green World Global, but from the four factors, personal factors have a significants effect on purchasing decisions with the results of the coefficient t count 1,729> t table 1,671 or it can be said the personal variables influence the purchasing decisions of Green World Global products.